2010
DOI: 10.1111/j.1939-1676.2009.0408.x
|View full text |Cite
|
Sign up to set email alerts
|

Whole Blood Manganese Concentrations in Dogs with Congenital Portosystemic Shunts

Abstract: Background: Manganese (Mn) is an essential mineral that is a cofactor for many enzymes required in the synthesis of proteins, carbohydrates, and lipids. Because hepatic clearance is essential in Mn homeostasis, conditions in humans resulting in hepatic insufficiency including cirrhosis and both acquired and congenital portosystemic shunting have been reported to result in increased blood Mn concentrations and increased Mn content in the central nervous system. Because Mn toxicity causes neurologic disturbances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 59 publications
(108 reference statements)
3
19
0
Order By: Relevance
“…This hypothesis is supported by our recent findings that dogs with cPSS have increased whole blood concentrations of manganese and that dogs with a cPSS have higher serum concentrations of C-reactive protein compared to dogs with a cPSS which were asymptomatic, observations which are similar to studies in human HE [9,11,30,31]. We investigated this hypothesis by measuring a range of clinical, haematological and biochemical variables, including plasma ammonia and sodium concentrations and systemic inflammatory response syndrome (SIRS) scores, in 120 dogs with a cPSS both with and without clinical signs of HE.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…This hypothesis is supported by our recent findings that dogs with cPSS have increased whole blood concentrations of manganese and that dogs with a cPSS have higher serum concentrations of C-reactive protein compared to dogs with a cPSS which were asymptomatic, observations which are similar to studies in human HE [9,11,30,31]. We investigated this hypothesis by measuring a range of clinical, haematological and biochemical variables, including plasma ammonia and sodium concentrations and systemic inflammatory response syndrome (SIRS) scores, in 120 dogs with a cPSS both with and without clinical signs of HE.…”
Section: Introductionsupporting
confidence: 70%
“…Longitudinal and provocative testing would be required to further investigate whether ammonia and inflammation play a causative role in spontaneous HE in dogs with a cPSS. In addition, we did not evaluate all other factors which have been linked to HE in dogs such as manganese [30], gastrointestinal derived endogenous benzodiazepines [46], hypercortisolism [47] and altered tryptophan metabolism [48]. However, our work clearly demonstrates that both ammonia and inflammation predicts the presence of HE in dogs with a cPSS and provides further evidence that dogs with a cPSS are a good spontaneous model of human HE, notably type B HE [1,49].…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated that the pathophysiology of HE in dogs with liver disease is very similar to human HE, with ammonia and inflammation playing a key role in the development of neurological abnormalities in dogs with a cPSS (Tivers et al 2014;Shawcross et al 2004Shawcross et al , 2007Gow et al 2012). Crucially, we have also demonstrated that dogs with a cPSS frequently have an increase in Mn concentrations (Gow et al 2010). Consequently, dogs with a cPSS are a highly informative, spontaneous model of human HE in which the pathogenesis of neurological complications associated with liver disorders can be explored without the need for the inducing liver disease in otherwise healthy animals.…”
Section: Introductionmentioning
confidence: 81%
“…Bile acid measurement was performed on an ILab 650 using a colorimetric, 2 point kinetic fixed time enzymatic reaction by Dialab. Whole blood Mn results from 14 previously reported dogs were used to define a range for healthy dogs (250-1052 μmol/L) (Gow et al 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Dogs with CPSS have increased whole blood manganese concentrations compared to healthy dogs . Blood manganese levels have not been reported in cats with HE.…”
Section: Current Veterinary Informationmentioning
confidence: 99%